Dietary Reference Values for vitamin B6 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal, 2016)
Abstract Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) derives Dietary Reference Values (DRVs) for vitamin B6. The Panel considers that plasma pyridoxal 5′‐phosphate (PLP) concentration is the biomarker of status suitable for deriving DRVs for vitamin B6. Considering that a plasma PLP concentration of 30 nmol/L, as a population mean, is indicative of an adequate vitamin B6 status, the Panel proposes to use this cut‐off value to set Average Requirements (ARs). Population Reference Intakes (PRIs) are derived for adults and children from ARs, assuming a coefficient of variation (CV) of 10%. For women, the AR and PRI are set at 1.3 and 1.6 mg/day. For men, the AR of 1.5 mg/day is derived by an allometric scaling from the AR for women, and a PRI of 1.7 mg/day is set. For all infants aged 7–11 months, an Adequate Intake of 0.3 mg/day is set, averaging the results of two extrapolation approaches based on an allometric scaling: upwards extrapolation from the estimated vitamin B6 intake of exclusively breastfed infants from birth to 6 months, and downwards extrapolation from the ARs for adults applying a growth factor. For all children, ARs are derived from adult ARs using an allometric scaling and growth factors. For children of both sexes aged 1–14 years, ARs range between 0.5 and 1.2 mg/day. For children aged 15–17 years, the Panel derives the same ARs as for adults. PRIs for children aged 1–17 years range between 0.6 and 1.7 mg/day. Extrapolation of ARs by an allometric scaling considered differences in reference body weight. For pregnant and lactating women, additional requirements are considered, based on the uptake of vitamin B6 by the fetal and maternal tissues and the losses through breast milk, and PRIs of 1.8 and 1.7 mg/day, respectively, are derived.